Religious actors and constitution drafting: the Philippines and the Arab awakening in comparative perspective. Issue 2 (3rd May 2016) - Buckley, David T.
Abstract: What strategies do religious elites pursue during potential regime transitions, and what explains this variation? A range of scholarship argues that religious groups, particularly Islamist movements, are prone to maximalist demands during potential transitions, particularly in moments of institutional indeterminacy like constitution drafting. In contrast, I distinguish two strategies open to religious elites in such periods: religious integralism and pious secularism. While religious integralists do attempt to merge state and religious institutions, pious secularists consent to some differentiation of these spheres while protecting a role for religion in post-transition public life. I argue that the choices of religious elites in these periods are heavily influenced by the status of relations with minority religions and secular portions of civil society, which are themselves structured by the prior authoritarian approach to the regulation of religion. I illustrate the framework with case studies drawn from the Arab Awakening (Tunisia and Egypt) and from two distinct periods within the Catholic-majority Philippines.